HUBUNGAN KOMPETENSI KEPRIBADIAN GURU BAHASA ARAB DENGAN MOTIVASI BELAJAR SISWA - Syafe'i, Isop; Maryani, Lenni Selvi (Program studi Pendidikan Bahasa Arab UNNES, 2020)
This study aims to determine the relationship of Arabic teacher personality with student motivation in learning Arabic. The research method used in this study uses a quantitative approach, and takes the population of students at MTs Darul Hidayah Bandung by using a sample of eighth grade students. Sampling was determined by random sampling technique. Data collection using the questionnaire method. While the analysis of statistical data with the Pearson correlation formula. The results showed that the relationship between the teacher's personal competence and student motivation in MTs Darul Hidayah in Bandung obtained a correlated significant value of 0.02 which was smaller than 0.05. The Pearson Correlation value between these two variables is of moderate correlation, with a value of 0.546 located between 0.41 to 0.60. In the comparison of Pearson Correlation with r table also achieved results that have a relationship with a value of 0.546 that is greater than 0.296 or it can be said the percentage of the relationship between the teacher's personal competency (X) with student motivation (Y) is 25%.